Exploring the potential for top-dressing bread wheat with ammonium chloride to minimize grain yield losses under drought. Issue 5 (3rd September 2018) - Kastury, Farzana; Rahimi Eichi, Vahid; Enju, Akiko; Okamoto, Mamoru; Heuer, Sigrid; Melino, Vanessa
ABSTRACT: The frequency and severity of drought is predicted to rise in many parts of the world. Considering that drought is the main constraint on rain-fed wheat crop production, both agronomic and genetic measures have been taken to minimize yield losses under drought. Beyond its role as a micronutrient, chloride also acts as an osmoticum, implicated in the regulation of stomatal aperture. This study explores the potential for chloride fertilization of Australian bread wheat ( Triticum aestivum L.) to minimize grain yield losses caused by drought stress. For this, two drought-tolerant commercial genotypes (Mace and Gladius) and a well-studied drought-tolerant genotype used in wheat breeding (RAC875) were treated with ammonium chloride, potassium chloride, or ammonium bicarbonate, the latter two treatments served as controls for chloride and ammonium, respectively. Plants were grown under either a watered or water-restricted (drought) regime. The genotype RAC875 was found to accumulate leaf chloride at a significantly higher level than the other genotypes under optimal growth conditions. Under drought conditions, top-dressing RAC875 plants with ammonium chloride resulted in up to a 2.5-fold increase in grain number and this effect was not seen when plants were top-dressed with either of the control fertilizers. The ammonium chloride treatment also minimized losses of grain yield in RAC875 plants grown under drought. Treatment effects were accompanied by an increase in stomatal conductance. These results collectively suggest that the compound fertilizer ammonium chloride can improve drought tolerance of wheat.